SURVEI ATAS IMPLEMENTASIGOOD UNIVERSITY GOVERNANCE Studi Kasus STAIN Pekalongan - Ahmad Rosyid; Agus Fakhrina; Miftahul Huda (JURNAL PENELITIAN, 2014)
The implementation of Good University Governance's principles (accountability and responsiveness), academic culture, academic's service quality and initiatives in the STAIN Pekalongan’s academic society was tested in this study. Data were collected from three main internal stakeholders (students, staffs, and lecturers) using questionnaire and their perception differences were analyzed using non parametric test of difference. The results show that (1) the total averages results placed between 7.34 to 9.89 which means that research variables were at a medium level (2) lecturers' perceptions differ significantly from both staffs and students.